4Ps system adopted in the learning process during the training of graduate students, teachers and researchers (Research, Society and Development, 2020)
With the advancement of education and the growing dispute for jobs, it has been noticed that graduation is no longer a guarantee of insertion in the job market. This has increased the number of people seeking graduate education. Stricto-Sensu graduate programs seek to meet teaching quality criteria in the training of masters, teachers and researchers, based on guidelines from the Coordination for the Improvement of Higher Education Personnel (CAPES). However, it is necessary for the graduate candidate to have a profile for scientific research, in addition to affinity with the area in question. Studies that show the main characteristics of the desired profile of graduate students are still incipient. Activities such as teaching internship, qualification and project defense, in addition to living with the supervisor, teachers and colleagues, generate in the student a series of expectations and adaptation to a new reality. These points are considered when choosing the area and line of research. Knowing activities attributed to graduate students is essential in decision making. The graduate students remain involved in activities and scientific research that require frequencies and tasks, which require an attitude based on attitudes, intellectual maturity, rigor, inflexibility, discipline, organization and rhythm. Thus, it is necessary to study organizational systems for academic life. The aim of this study was to guide characteristics related to the profile of students entering the Stricto-Sensu graduate program, referred to here as the 4Ps system; describe activities of graduate students; and, develop a strategic system adopted in the learning process during the training of masters, teachers and researchers from lived experiences.